2005
DOI: 10.1111/j.1460-9568.2005.03980.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurons expressing relaxin 3/INSL 7 in the nucleus incertus respond to stress

Abstract: Relaxin 3/INSL 7 has recently been identified as a new member of the insulin/relaxin superfamily. Although it was reported to be dominantly expressed in the brain, its detailed distribution and function in the central nervous system are still obscure. In the present study we demonstrated that in the rat relaxin 3 was mainly expressed in neurons of the nucleus incertus (NI) of the median dorsal tegmental pons. Other relaxin 3-expressing neurons were scattered in the pontine raphe nucleus, the periaqueductal gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
430
0
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(458 citation statements)
references
References 38 publications
21
430
0
7
Order By: Relevance
“…In the clinical setting, there is high comorbidity between substance abuse and stress-related psychiatric disorders such as depression (47). Our studies suggest a role for the relaxin-3/ RXFP3 system, which has established interactions with CRF signaling (20,26), in mediating interactions between stress and drugseeking. In particular, RXFP3 signaling in the BNST appears to influence stress-related alcohol-seeking behavior.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In the clinical setting, there is high comorbidity between substance abuse and stress-related psychiatric disorders such as depression (47). Our studies suggest a role for the relaxin-3/ RXFP3 system, which has established interactions with CRF signaling (20,26), in mediating interactions between stress and drugseeking. In particular, RXFP3 signaling in the BNST appears to influence stress-related alcohol-seeking behavior.…”
Section: Discussionmentioning
confidence: 75%
“…Relaxin-3 is predominantly expressed in gamma-aminobutyric acid (GABA) neurons in the hindbrain nucleus incertus, which projects widely to forebrain areas, including the amygdala, bed nucleus of the stria terminalis (BNST), hippocampus, and lateral hypothalamus, which also express high levels of RXFP3 (11,15,(17)(18)(19)(20)(21)(22). This pattern of innervation, along with findings that relaxin-3 can modulate (i) food intake (23)(24)(25), (ii) responses to stress (20,26,27), (iii) arousal (28,29), and (iv) interactions with the corticotropin-releasing factor (CRF) systems (20,26), led us to hypothesize that relaxin-3 may modulate aspects of behavior related to substance use and abuse. Such a role would parallel that of other neuropeptides, such as orexin/hypocretin (30,31), galanin (32), and melanin-concentrating hormone (33).…”
Section: Addiction | Dependencementioning
confidence: 99%
See 1 more Smart Citation
“…Relaxin-3 and its receptor GPCR135 are both predominantly expressed in the brain (11,14), in particular in regions dealing with sensory signals (15,16). This finding, together with recent in vivo studies that revealed that relaxin-3 is involved in stress responses (17) and in regulation of feeding (18), suggest a physiological role in neuroendocrine and sensory processing. An interesting feature of relaxin-3 is its ability to activate both GPCR142 (19) and LGR7 (20) in addition to its own receptor, GPCR135 (11).…”
mentioning
confidence: 60%
“…The largest population of relaxin-3 expressing neurons is located within the tegmental area known as the nucleus incertus (NI), and these neurons project broadly throughout the brain [15][16][17][18][19]. The neuroanatomy of the relaxin-3/RXFP3 system suggests a broad role as an ascending neuromodulatory network [20,21], akin to the monoamine systems including serotonin, and noradrenaline [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%